PENERAPAN PASAL 4 UNDANG-UNDANG NO. 8 TAHUN 1999 TERHADAP PRODUK BERAS YANG MENGANDUNG KLORIN (PEMUTIH) DI KABUPATEN BANYUMAS - Suyadi Suyadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2011)
Technology and science development influenced the producers to give various innovation in their products. This innovation did not often coincide with the product guarantee quality to consume, that is by mixing dangerous chemical substances. Rice, the steple food, is also mixed with chlorine which is very dangerous. That is why, this research aim is to know how law protection for consumers towards rice containing the chlorine in Banyumas Regency. The result of the research showed that basesd on the norms which were supported by the interviews with related informants, so most consumers’ rights had been fulfilled because of the obligation of the product quality standard fulfillment represented in Act No. 7, 1996, prohibition of dangerous chemical substance in Permentan No. 32/Permentan/OT.140/3/2007, and product supervision and development represented in Kepmenperindag Nomor 634/MPP/Kep/9/2002, and sanction or administration punishment for the producers who break the law. Keywords: implementation, chlorine, Act No 8, 1999